Concentrations of Progesterone (P4), Anti-Müllerian Hormone (AMH), and Haptoglobin (Hp) in Pregnant and Non-Pregnant Ewes and Their Association with Fetal Mortality, Maternal Weight, and Twinning Rate - Halil Gunes Ozturan; Selim Aslan; Feride Zabitler Tepik; Isfendiyar Darbaz; Serkan Sayiner; Axel Wehrend (Veterinary Sciences)
The study groups (n = 39) included ewes with ongoing pregnancy (P+; n = 19), with fetal death (FD; n = 12), and that were not pregnant (P−; n = 8). Blood samples were taken on days 10, 20, 30, 40, 60, 80, and 150 post-mating. Ultrasonography (USG) controls started on day 30. The P4 concentrations differed significantly between P+ and P− on all days (p < 0.001). Regarding AMH concentrations, a significant difference was observed between P+ and P− on day 30. P4 increased significantly from day 60 to 80 and remained elevated until day 150 in P+, while remaining basal in P−. In FD and P− groups, P4 reached its lowest concentrations. A rapid decrease in P4 was observed in P− from day 20 onwards. A statistically significant difference in P4 was also noted between P+ and FD. Additionally, P4 concentrations differed between singleton and twin pregnancies, especially on days 20 and 40. Statistically significant differences in AMH were found between P+ and FD on days 10, 20, and 30. In P+ sheep, P4, AMH, and Hp concentrations varied by season. A significant relationship was found between AMH and Hp concentrations and body weight. In conclusion, P4 stands out as the primary marker for distinguishing pregnancy status and detecting embryonic loss, while AMH provides complementary support, particularly in identifying fetal death. Seasonal changes were reflected across P4, AMH, and Hp concentrations, with AMH and Hp also showing significant associations with BW.